BERKEADILAN YANG DILAKUKAN OLEH POLRI (Telaah Filsafat Hukum) - Saragih, Bonarsius (Sekolah Tinggi Hukum Bandung, 2010)
Law enforcement as facility to create the direction of law should be applied as effective as possible to create morality values in law. The failure of law is a very dangerous threat to the decrease of law itself. The law which does not have good implementation to morality values will be far and isolated from societies. The success of law enforcement will be a barometer of law legitimacy in the social reality. The law culture of law enforcement, especially Indonesian Republic State Police (POLRI) in performing their duties and their authorities as investigators still have violation culture; false arrest, incorrect procedure. Scrutinizing philosophy principle from process law (KUHAP), the function of law enforcement entrusted to Indonesian Republic State Police (POLRI) exists in the scope of performance of Gods mandate.The must be courageous, and must have ability to scrutinize and understand the signal of consistent justice values with conception of Gods justice values and human justice which is always created in every law enforcement. Law enforcement performed by Indonesian Republic State Police should perform good law enforcement by principles of: leaving non scientific investigation and always using examination pattern of scientific investigation; leaving incusator examination, but acusator way and also upholding presumption of innocence principleKeywords: Justice Indonesian Police Legal Philosophy